2019
DOI: 10.1155/2019/5949232
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and Biocompatibility of an Eggshell-Derived Hydroxyapatite Material Modified with Si/PLGA for Bone Regeneration in Dentistry

Abstract: Hydroxyapatite (HAp) is the most commonly used biomaterial in modern bone regeneration studies because of its chemical similarity to bone, biocompatibility with different polymers, osteoconductivity, low cost, and lack of immune response. However, to overcome the disadvantages of HAp, which include fragility and low mechanical strength, current studies typically focus on property modification through the addition of other materials. Objective. To develop and evaluate the biocompatibility of a HAp material extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 64 publications
(82 reference statements)
0
16
0
4
Order By: Relevance
“…Out of 71 relevant article titles collected from SCOPUS, PubMed, and Google Scholar, only 36 were included after screening the title, abstract, and content for in vitro degradation and cytotoxicity testing for the biocompatibility of eggshell-based hydroxyapatite. The articles came from several countries, such as India [ 11 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], Bangladesh [ 41 , 42 ], China [ 43 ], Korea [ 25 , 44 , 45 ], Turkey [ 46 , 47 , 48 ], Thailand [ 49 , 50 ], Brazil [ 26 ], Italy [ 51 ], USA [ 52 ], Romania [ 2 ], Vietnam [ 53 , 54 ], Colombia [ 55 ], and Egypt [ 56 ]. The study selection of the articles included in the systematic review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 71 relevant article titles collected from SCOPUS, PubMed, and Google Scholar, only 36 were included after screening the title, abstract, and content for in vitro degradation and cytotoxicity testing for the biocompatibility of eggshell-based hydroxyapatite. The articles came from several countries, such as India [ 11 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], Bangladesh [ 41 , 42 ], China [ 43 ], Korea [ 25 , 44 , 45 ], Turkey [ 46 , 47 , 48 ], Thailand [ 49 , 50 ], Brazil [ 26 ], Italy [ 51 ], USA [ 52 ], Romania [ 2 ], Vietnam [ 53 , 54 ], Colombia [ 55 ], and Egypt [ 56 ]. The study selection of the articles included in the systematic review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The statistical significance of the difference between the control and treatment groups was evaluated using a one-way analysis of variance (ANOVA) [ 45 ]. The quantification of viable cells was evaluated with the help of fluorescence microscopy [ 2 , 25 , 26 ], field emission scanning electron microscopy (FESEM) [ 52 ], and scanning electron microscopy [ 55 ]. The optical density test results from articles [ 2 , 20 , 49 , 50 ] are displayed in Figure 4 with a comparison of the control samples and treatment material variations, which can be used to determine the value of cell viability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each test is carried out thrice and the IC50 of the test samples as the percentage survival of the cells are calculated. (Gutiérrez-Prieto et al, 2019) Invitro Bromodeoxyuridine (BrDu) cell proliferation assay: The 10 mM stock solution of BrdU assay is prepared by dissolving 3 mg of BrdU in 1 mL of water. Then, the 10 mM BrdU stock solution is diluted into a cell culture medium which forms a 10 µM BrdU of labeling solution.…”
Section: Cell Viability By Mtt Assaymentioning
confidence: 99%
“…HAp can be obtained by two main ways: (1) synthesis from compounds containing calcium and phosphorus [6]; (2) extraction from natural sources including corals [11][12][13], cuttlefish bones [14][15][16][17][18], seashells from clams, oysters, snails [19][20][21][22][23], eggshell [24,25], mammalian bone (e.g. bovine [26,27], camel and horse [28]), fish scales [29][30][31][32], and fish bones [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%